2014
DOI: 10.1007/s12678-014-0233-y
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Nanocrystalline IrO2-Based Catalysts in Parallel Chlorine and Oxygen Evolution

Abstract: This paper examines the detection and quantification of the potentially corrosive byproducts of the oxygen evolution reaction on iridium and iridium-ruthenium mixed oxides. A conventional but stationary ring-disc electrode was employed in a flow cell configuration for the detection of volatile reaction product other than oxygen, and the formation of at least two active species was detected.Potential-modulated UV-VIS reflectance spectroscopy helped to identify one of these volatile reaction byproducts as hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…[4] Regrettably, the oxygen evolution reaction (OER) constitutes a detrimental anodic side reaction under CER conditions. [5][6][7][8] Even though conventionally applied dimensionally stable anodes (DSAs) [9][10][11] reveal CER selectivity of about 97-99 %, [12] the gaseous products Cl 2 and O 2 need to be separated from each other, corresponding to a significant fraction of the overall process costs. [13,14] Therefore, the development of an electrode material that is as stable as DSAs under the harsh anodic reaction conditions, but reveals higher CER selectivity than DSAs, is an ultimate dream of chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Regrettably, the oxygen evolution reaction (OER) constitutes a detrimental anodic side reaction under CER conditions. [5][6][7][8] Even though conventionally applied dimensionally stable anodes (DSAs) [9][10][11] reveal CER selectivity of about 97-99 %, [12] the gaseous products Cl 2 and O 2 need to be separated from each other, corresponding to a significant fraction of the overall process costs. [13,14] Therefore, the development of an electrode material that is as stable as DSAs under the harsh anodic reaction conditions, but reveals higher CER selectivity than DSAs, is an ultimate dream of chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The anode material consists of Ti plates coated with TiO 2 À RuO 2 mixed oxides, commonly denoted as dimensionally stable anodes (DSA). [5][6][7] RuO 2 has been identified as active component of the DSA for electrochemical chlorine evolution (CER), [8] which is impaired by a selectivity problem: the evolution of gaseous oxygen (OER) is a competing side reaction in the same potential window of CER, [9][10][11][12][13] which from a thermodynamic point of view is even preferred over CER according to the smaller equilibrium potential.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine evolution is thermodynamically less favorable than oxygen evolution, but because it is atwo-electron process rather than the four electrons required for OER, chlorine production is less kinetically hindered and thus can be more favorable than oxygen production. [57,[59][60][61] Oxygen-selective catalysts in acidic chlorinated conditions are relatively underexplored, yet afew promising early studies have reported selectivity for oxygen production from seawater by using doped manganese oxides. [58] Catalyst activities for OER and CER were initially found to follow the same trends,inwhich better OER catalysts were also better CER catalysts,b ut more recent studies have tuned the selectivity of OER over CER by adjusting the catalystse lectronic structure using dopants.…”
Section: Summary Of Membrane-based Pretreatment Processes For Brine Vmentioning
confidence: 99%
“…[57] Indeed, CER is typically favored over OER at acidic conditions. [62,63] More recent work used similar doped manganese oxides [52,64] and other doped oxides [59,61,65] to selectively produce oxygen even under acidic brine conditions with reasonable selectivity. [57,[59][60][61] Oxygen-selective catalysts in acidic chlorinated conditions are relatively underexplored, yet afew promising early studies have reported selectivity for oxygen production from seawater by using doped manganese oxides.…”
Section: Summary Of Membrane-based Pretreatment Processes For Brine Vmentioning
confidence: 99%
See 1 more Smart Citation